2018
DOI: 10.20944/preprints201810.0554.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microbiome – The Missing Link in the Gut-Brain Axis. The Focus on Gastrointestinal and Mental Health

Abstract: The central nervous system (CNS) and the human gastrointestinal (GI) tract communicate through the gut-brain axis (GBA). Such communication is bi-directional and involves neuronal, endocrine and immunological mechanisms. The scientific data are mounting that gut microbiota is a source of a number of neuroactive and immunocompetent substances, which shape the structure and function of brain regions involved in control of emotions, physical activity and cognition. Most of GI maladies are associated with altered … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Numerous data demonstrate the impact of probiotics on human health and the potential for their use in the prevention and treatment of many diseases [5,8,10,16,[27][28][29][30]. Probiotic preparations are recognized as safe for health.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous data demonstrate the impact of probiotics on human health and the potential for their use in the prevention and treatment of many diseases [5,8,10,16,[27][28][29][30]. Probiotic preparations are recognized as safe for health.…”
Section: Discussionmentioning
confidence: 99%
“…Ahmed et al 44 reported an eight times greater prevalence of ASD in HI children compared to a typical comparison group which is similar to the 14 times higher prevalence rates reported for the HI studies in this review. When compared qualitatively to the prevalence of ASD in the general population of 0.6-1.0% [9][10][11][59][60][61][62][63] there is a greater likelihood of ASD in the presence of VI or HI. These findings strongly support the need for greater surveillance of ASD in children with congenital VI or HI.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence rates were compared between the included studies reporting ASD and VI or HI with prevalence rates for ASD in the general population. 10,11,[59][60][61][62][63] Tables 3 and 4 list the included studies for VI and HI prevalence rates respectively with the details of the best matched comparison populations from which prevalence rates were compared to estimate the relative risk ratios (RR). See Figures 5 and 7.…”
Section: Methodsmentioning
confidence: 99%